Art at the Biomedical Interface: Trans/Sculptural Discourses in Guillem Viladot's Ruth. (4th July 2018) - Johnson, P. Louise
Abstract: The short epistolary novel Ruth by Guillem Viladot was published posthumously in 2000 and received only brief press mention, in spite of its singular treatment of the subject of transsexuality which set it apart within the Catalan and Spanish literary panorama of the time. The portrayal of the psychological and emotional struggle experienced by the artist and sculptor Ruth before and after surgery, is heavily inflected by Viladot's interest in Lacanian psychoanalysis, and runs in parallel with a discourse on the process of artistic creation. This article examines the way in which art functions as a metaphor for an alternative endpoint (or at least outcome) of transitioning, which is ultimately more optimistic than the reality confronted by Ruth as she slides into psychosis. Drawing on the recent work of psychoanalyst Oren Gozlan which seeks to understand transsexuality as a creative act, the article argues that Viladot is prescient in seeing the possibilities in aesthetic discourse for our understanding of sexual difference and identity. At the same time, with reference to Middlesex (2002) by Jeffrey Eugenides and its criticism, it underscores the contemporary relevance of the novel in questioning the still dominant sex/gender binary and cultural backwardness characteristic of debates around transsexuality.